Real-World Evidence of Clinical Outcomes of the Use of the Adalimumab Biosimilar SB5 in Rheumatic and Gastrointestinal Immune-Mediated Inflammatory Diseases: 12-Month Data from the PERFUSE Study - Bruno Fautrel; Yoram Bouhnik; Carine Salliot; Franck Carbonnel; Mathurin Fumery; Christophe Bernardeau; Yves Maugars; Mathurin Flamant; Fabienne Coury; Ben Braithwaite; Salima Hateb; Janet Addison; et al. (Drugs - Real World Outcomes)
Abstract Background There is a need for published data on real-world use of SB5, an adalimumab (ADL) biosimilar approved in Europe in 2017, on the basis of evidence from pre-clinical and analytic data as well as phase I and III clinical studies demonstrating equivalent efficacy and comparable pharmacokinetics, safety and immunogenicity profiles as the reference ADL. Objectives The purpose of this study was to estimate patient persistence on SB5 at 12 months post-initiation using clinical and healthcare claims data from the French Système National des Données de Santé (national healthcare claims database, SNDS) in addressing data gaps. Methods PERFUSE is a 12-month, observational, multi-centre cohort study of patients with rheumatic or gastrointestinal immune-mediated inflammatory diseases (IMIDs) who initiated routine SB5 treatment between October 2018 and October 2020, either as their first ADL (naïve) or transitioning from another ADL (switched). Clinical data, including disease activity scores, C-reactive protein levels, and dosing information, were collected as available from patient records captured during routine visits to specialist physicians. Persistence data were supplemented with data from the French SNDS. Analyses of clinical data were descriptive, while persistence was assessed using a Kaplan–Meier survival analysis. Results Overall, 911 patients were included: 507 from rheumatology centres [116 with rheumatoid arthritis (RA), 78 psoriatic arthritis (PsA), and 313 ankylosing spondylitis (AS)] and 404 from gastroenterology centres [316 with Crohn’s disease (CD) and 88 ulcerative colitis (UC)]. Among naïve patients, 12-month remission/low activity rates were 58% for RA, 66% for PsA, 59% for AS, 94% for CD, and 85% for UC, increasing significantly from baseline for all indications (p < 0.05). Switched patients’ remission rates remained stable between baseline and month 12 (M12) for all indications (p > 0.05). Persistence (95% CI) at M12 among naïve patients was 59% (46.5, 68.8) for RA, 65% (49.7, 77.1) for PsA, 56% (48.3, 62.6) for AS, 70% (63.0, 75.7) for CD, and 42% (30.7, 53.1) for UC, compared to 60% (42.7, 73.7) for RA, 57% (37.3, 72.1) for PsA, 55% (45.8, 64.0) for AS, 63% (53.4, 71.7) for CD, and 56% (27.2, 77.6) for UC among switched patients. No significant differences were observed between naïve and switched patients (p > 0.05). SNDS pairing provided information on 68 of the 132 patients (52%) who were lost to follow-up in the clinical database, of whom 57 (84%) were confirmed persistent at M12 and 11 (16%) non-persistent. Primary treatment failure (naïve patients) and patient decision (switched patients) were the most common reasons stated for treatment discontinuation. Conclusions SB5 provides clinically effective treatment of both gastrointestinal and rheumatic IMIDs for ADL-naïve and switched patients, with no loss of control observed when switching. Persistence was comparable between naïve and switched populations, though the reasons for non-persistence differed. Trial Registry Trial registration number: Clinical Trials identifier NCT03662919. Trial registration date: 10 September 2018.